A sealing solution for carbon / ceramic friction disc and a sealing method and a dense carbon / ceramic friction disc and its application
Patent Information
- Application Number
- CN202610817410.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-05
- Publication Date
- 2026-08-28
AI Technical Summary
[0002]碳/陶摩擦盘因低密度、高耐热性、优异的摩擦性能,成为高端制动/传动领域的核心部件,渗硅工艺是碳/陶摩擦盘制备的常用手段,通过渗硅可在碳/陶基体中形成SiC相,提升基体力学性能与耐磨性,但渗硅后摩擦面易残留游离硅,游离硅的存在会导致摩擦盘使用过程中摩擦系数波动大、高温抗氧化性下降,因此需对摩擦盘进行去硅预处理,再通过浸渍封孔工艺重点实现摩擦面的致密化改性,保障碳/陶摩擦盘的制动/传动性能
(1)界面结合力与高温稳定性大幅提升:本发明采用液态聚碳硅烷-液态聚硼硅氮烷调配聚合物溶液,裂解固化后形成SiC-Si3N4多元陶瓷相,Si3N4的低膨胀特性使多元陶瓷相的热膨胀系数与碳/陶摩擦盘基体高度匹配,大幅降低高温下的界面热应力;同时,界面增强金属组分与碳/陶摩擦盘基体及SiC发生原位反应形成金属间化合物,在封孔层与基体之间形成柔性过渡层,实现机械啮合+化学结合的双重结合模式,使常温层间剪切强度提升至35~45MPa,彻底解决了现有工艺高温界面结合力差、易层间剥离的技术问题。
Smart Images

Figure CN122647236A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of carbon / ceramic composite material preparation technology, and in particular to an impregnation and sealing liquid for a carbon / ceramic friction disk, an impregnation and sealing method, a densified carbon / ceramic friction disk, and its application. Background Technology
[0002] Carbon / ceramic friction discs, due to their low density, high heat resistance, and excellent friction performance, have become core components in high-end braking / transmission applications. Silicon infiltration is a common method for preparing carbon / ceramic friction discs. By infiltrating, a SiC phase can be formed in the carbon / ceramic matrix, improving the mechanical properties and wear resistance of the matrix. However, free silicon is easily left on the friction surface after silicon infiltration. The presence of free silicon can lead to large fluctuations in the friction coefficient and a decrease in high-temperature oxidation resistance during the use of the friction disc. Therefore, it is necessary to perform silicon removal pretreatment on the friction disc and then use an impregnation and sealing process to focus on achieving densification modification of the friction surface to ensure the braking / transmission performance of the carbon / ceramic friction disc.
[0003] Currently, the impregnation and sealing process for carbon / ceramic friction discs mostly uses a single polycarbosilane as a precursor. Although it can achieve basic densification by forming a SiC ceramic phase through impregnation-pyrolysis, there are obvious technical shortcomings: the friction stability and high-temperature oxidation resistance of the single polycarbosilane sealing layer are limited, making it difficult to meet the requirements of carbon / ceramic friction discs for long-term use under extreme braking / clutch transmission conditions of 600~1650℃, high load, and high speed difference. Summary of the Invention
[0004] In view of this, the object of the present invention is to provide an impregnation and sealing solution for carbon / ceramic friction discs, an impregnation and sealing method, and a densification method for carbon / ceramic friction discs. The impregnation and sealing solution for carbon / ceramic friction discs provided by the present invention can improve the high-temperature oxidation resistance of carbon / ceramic friction discs.
[0005] To achieve the above-mentioned objectives, the present invention provides the following technical solution: This invention provides an impregnation and sealing solution for a carbon / ceramic friction disc, comprising the following components in weight percentage: Interface-reinforcing metal component 2-5%, friction-resistant ceramic component 3-6%, metal oxide component 2-5%, balance polymer; The polymer comprises liquid polycarbosilane and liquid polyborosilicate, wherein the mass ratio of liquid polycarbosilane to liquid polyborosilicate is 7~9:1~3; The interface-enhancing metal component includes one or more of titanium powder, chromium powder, nickel powder, cobalt powder, and molybdenum powder; The friction-resistant ceramic component includes one or more of silicon carbide, zirconium boride, boron carbide, and zirconium carbide; The metal oxide component includes one or more of cerium oxide, yttrium oxide, and lanthanum oxide.
[0006] Preferably, the total mass percentage of the interface-enhancing metal component, the tribologically resistant ceramic component, and the metal oxide component does not exceed 15%.
[0007] This invention also provides a method for preparing the impregnation and sealing liquid for the carbon / ceramic friction disk described in the above technical solution, comprising the following steps: The polymer, interface-reinforcing metal component, friction-resistant ceramic component, and metal oxide component are mixed and dispersed to obtain the impregnation and sealing liquid for the carbon / ceramic friction disk.
[0008] Preferably, the composite dispersion is carried out under ultrasonic and stirring conditions, wherein the ultrasonic power is 300~500W, the stirring speed is 800~1200r / min, and the composite dispersion time is 40~80min.
[0009] The present invention also provides a method for impregnating and sealing carbon / ceramic friction discs, comprising the following steps: The carbon / ceramic friction disk is pretreated with desiliconization to obtain a pretreated carbon / ceramic friction disk; The pretreated carbon / ceramic friction disk is impregnated and sealed in a composite impregnation solution to obtain an impregnated carbon / ceramic friction disk. The impregnated carbon / ceramic friction disk is pyrolyzed and solidified to obtain a densified carbon / ceramic friction disk. The composite impregnation liquid is the impregnation and sealing liquid for carbon / ceramic friction disks described in the above technical solution or the impregnation and sealing liquid for carbon / ceramic friction disks prepared by the preparation method described in the above technical solution.
[0010] Preferably, the residual silicon content of the carbon / ceramic friction disc is 8~15 wt.%; The desiliconization pretreatment method is acid etching or heat treatment; The heat treatment temperature is 1600~1800℃, the vacuum degree is <100Pa, and the time is 50~70min; The reagent used for acid etching is a mixed acid, which includes hydrofluoric acid and nitric acid. The volume ratio of hydrofluoric acid to nitric acid in the mixed acid is 1:2~4. The mass concentration of hydrofluoric acid is greater than or equal to 40%, and the mass concentration of nitric acid is 65~68%. The acid etching time is 90~150 min.
[0011] Preferably, the impregnation and sealing pressure is 1.2~2.0MPa and the time is 60~120min.
[0012] Preferably, the pyrolysis curing temperature is 1250~1450℃, the rate of heating to the pyrolysis curing temperature is 5~10℃ / min, and the holding time is 2~4h.
[0013] The present invention also provides a densified carbon / ceramic friction disc obtained by the impregnation and sealing method described in the above technical solution.
[0014] The present invention also provides the application of the densified carbon / ceramic friction disc described in the above technical solution in high-speed braking or clutch transmission components.
[0015] This invention provides an impregnation and sealing liquid for a carbon / ceramic friction disc.
[0016] Compared with the prior art, the present invention has the following significant advantages: (1) Significantly improved interfacial bonding and high-temperature stability: This invention uses liquid polycarbosilane-liquid polyborosilicate to prepare polymer solution, which is then cracked and solidified to form SiC-Si3N4 multi-element ceramic phase. The low expansion characteristics of Si3N4 make the thermal expansion coefficient of the multi-element ceramic phase highly matched with the carbon / ceramic friction disk matrix, which significantly reduces the interfacial thermal stress at high temperature. At the same time, the interfacial reinforcing metal component reacts in situ with the carbon / ceramic friction disk matrix and SiC to form intermetallic compounds, forming a flexible transition layer between the sealing layer and the matrix, realizing a dual bonding mode of mechanical meshing and chemical bonding, which increases the interlayer shear strength at room temperature to 35~45MPa, and completely solves the technical problems of poor high-temperature interfacial bonding and easy interlayer peeling in the existing process.
[0017] (2) Synergistic optimization of friction stability and wear resistance: The friction wear-resistant ceramic component has a hardness ≥1600HV, which can effectively stabilize the transfer film on the friction surface of the carbon / ceramic friction disc and suppress the fluctuation of the friction coefficient during braking. At the same time, the component is interwoven with SiC-Si3N4 multi-element ceramic phase, which significantly improves the density and surface hardness of the sealing layer, greatly reduces the wear rate of the friction surface, and extends the actual service life of the carbon / ceramic friction disc.
[0018] (3) Significantly enhanced high-temperature oxidation resistance: The nanoscale metal oxide component can refine the grains of the ceramic phase after pyrolysis and solidification, reduce grain boundary defects, and inhibit oxygen penetration along the grain boundary; at the same time, the metal oxide and SiC and Si3N4 work together to block oxidation channels and significantly improve the high-temperature oxidation resistance of the sealing layer; the B and N elements introduced after the pyrolysis and solidification of polyborosilicate further optimize the high-temperature performance of the ceramic phase, enabling the carbon / ceramic friction disc to withstand long-term high-temperature braking conditions above 1300℃, and the mass loss rate after 10h of high-temperature oxidation at 1300℃ is ≤0.4%.
[0019] The impregnation and sealing liquid for carbon / ceramic friction discs provided by this invention can achieve a triple improvement in the interfacial bonding force, friction stability, and high-temperature oxidation resistance of carbon / ceramic friction discs. It has strong process compatibility and is suitable for industrial mass production. It can be used in the manufacturing of core friction components in aerospace, high-end equipment and other fields such as high-speed braking / transmission systems. Typical application scenarios include, but are not limited to, aircraft brake discs, aircraft engine clutch discs, and automotive high-speed clutch discs. Attached Figure Description
[0020] Figure 1 Flowchart of the impregnation and sealing method for the carbon / ceramic friction disk provided by the present invention; Figure 2 The image shows the surface morphology of the densified carbon / ceramic friction disc after a friction test in Example 1. Figure 3 The curve showing the relationship between the dry friction coefficient and time for the densified carbon / ceramic friction disc of Example 1 is shown. Figure 4 The images show the surface morphology of the densified carbon / ceramic friction disc after the friction test in Comparative Example 1. The left image is the outer side image, and the right image is the inner side image. Detailed Implementation
[0021] This invention provides an impregnation and sealing solution for a carbon / ceramic friction disc, comprising the following components in weight percentage: Interface-reinforcing metal component 2-5%, friction-resistant ceramic component 3-6%, metal oxide component 2-5%, balance polymer; The polymer comprises liquid polycarbosilane and liquid polyborosilicate, wherein the mass ratio of liquid polycarbosilane to liquid polyborosilicate is 7~9:1~3; The interface-enhancing metal component includes one or more of titanium powder, chromium powder, nickel powder, cobalt powder, and molybdenum powder; The friction-resistant ceramic component includes one or more of silicon carbide, zirconium boride, boron carbide, and zirconium carbide; The metal oxide component includes one or more of cerium oxide, yttrium oxide, and lanthanum oxide.
[0022] Unless otherwise specified, the raw materials used in this invention are preferably commercially available products.
[0023] The impregnation and sealing solution for the carbon / ceramic friction disk provided by this invention includes an interface-reinforcing metal component with a mass percentage of 2-5%, specifically preferably 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, or 5%. In this invention, the interface-reinforcing metal component includes one or more of titanium powder (Ti), chromium powder (Cr), nickel powder (Ni), cobalt powder (Co), and molybdenum powder (Mo), preferably a mixed powder of titanium powder, chromium powder, and nickel powder, wherein the mass ratio of titanium powder, chromium powder, and nickel powder in the mixed powder is preferably 4:4:2. In this invention, the interface-reinforcing metal component can react in situ with the carbon / ceramic friction disk and SiC to form intermetallic compounds, reducing the difference in the interfacial thermal expansion coefficients.
[0024] The impregnation and sealing solution for the carbon / ceramic friction disc provided by this invention comprises a friction-wear-resistant ceramic component with a mass percentage of 3-6%, specifically preferably 3%, 3.5%, 4%, 4.5%, 5%, 5.5%, or 6%. In this invention, the friction-wear-resistant ceramic component comprises one or more of silicon carbide (SiC), zirconium boride (ZrB2), boron carbide (B4C), and zirconium carbide (ZrC), preferably a mixed powder of silicon carbide, zirconium boride, and zirconium carbide, wherein the mass ratio of silicon carbide, zirconium boride, and zirconium carbide in the mixed powder is preferably 5:3:2. In this invention, the hardness of the friction-wear-resistant ceramic component is ≥1600 HV. In this invention, the friction-wear-resistant ceramic component can stabilize the transfer film on the carbon / ceramic friction surface and improve the wear resistance of the friction surface.
[0025] The impregnation and sealing solution for the carbon / ceramic friction disc provided by this invention comprises a metal oxide component with a mass percentage of 2-5%, specifically preferably 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, or 5%. In this invention, the metal oxide component includes one or more of cerium oxide (CeO2), yttrium oxide (Y2O3), and lanthanum oxide (La2O3), preferably a mixed powder of cerium oxide and yttrium oxide, wherein the mass ratio of cerium oxide to yttrium oxide in the mixed powder is preferably 3:2. In this invention, the metal oxide component can refine ceramic grains and improve the high-temperature oxidation resistance and interfacial compatibility of the sealing layer.
[0026] In this invention, the total mass percentage of the interface-reinforcing metal component, the friction-resistant ceramic component, and the metal oxide component is preferably no more than 15%, more preferably 5-15%, and specifically preferably 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, or 15%.
[0027] The impregnation and sealing liquid for the carbon / ceramic friction disc provided by the present invention includes a balance of polymer, wherein the polymer comprises liquid polycarbosilane and liquid polyborosilazane, and the mass ratio of liquid polycarbosilane to liquid polyborosilazane is 7~9:1~3, preferably 7:3, 8:2 or 9:1, and more preferably 8:2. In this invention, the number-average molecular weight of the liquid polycarbosilane is preferably 600-1200 g / mol, specifically preferably 600 g / mol, 700 g / mol, 800 g / mol, 900 g / mol, 1000 g / mol, 1100 g / mol, or 1200 g / mol; the number-average molecular weight of the liquid polyborosilicate is preferably 700-1500 g / mol, specifically preferably 700 g / mol, 800 g / mol, 900 g / mol, 1000 g / mol, 1100 g / mol, 1200 g / mol, 1300 g / mol, 1400 g / mol, or 1500 g / mol. In this invention, a mass ratio of liquid polycarbosilane to liquid polyborosilicate of 7-9:1-3 achieves an optimal balance between polymer wettability, thermal expansion matching of the ceramic phase after pyrolysis and solidification, and preparation cost.
[0028] This invention also provides a method for preparing the impregnation and sealing liquid for the carbon / ceramic friction disk described in the above technical solution, comprising the following steps: The polymer, interface-reinforcing metal component, friction-resistant ceramic component, and metal oxide component are mixed and dispersed to obtain the impregnation and sealing liquid for the carbon / ceramic friction disk.
[0029] In this invention, the particle size of the interface-reinforcing metal component is preferably 50-200 nm. In this invention, the particle size of the tribological wear-resistant ceramic component is preferably 100-500 nm. In this invention, the particle size of the metal oxide component is preferably 50-100 nm.
[0030] In this invention, the composite dispersion is carried out under ultrasonic and stirring conditions. The ultrasonic power is preferably 300-500W, more preferably 400W; the stirring speed is preferably 800-1200 r / min, more preferably 1000 r / min; and the composite dispersion time is preferably 40-80 min, more preferably 60 min. In this invention, the composite dispersion ensures that each functional component is uniformly dispersed in the polymer, avoiding agglomeration.
[0031] The present invention also provides a method for impregnating and sealing carbon / ceramic friction discs, comprising the following steps: The carbon / ceramic friction disk is pretreated with desiliconization to obtain a pretreated carbon / ceramic friction disk; The pretreated carbon / ceramic friction disk is impregnated and sealed in a composite impregnation solution to obtain an impregnated carbon / ceramic friction disk. The impregnated carbon / ceramic friction disk is pyrolyzed and solidified to obtain a densified carbon / ceramic friction disk. The composite impregnation liquid is the impregnation and sealing liquid for carbon / ceramic friction disks described in the above technical solution or the impregnation and sealing liquid for carbon / ceramic friction disks prepared by the preparation method described in the above technical solution.
[0032] This invention involves pretreating a carbon / ceramic friction disk by desiliconization to obtain a pretreated carbon / ceramic friction disk. In this invention, the residual silicon content of the carbon / ceramic friction disk is preferably 8-15 wt.%, specifically preferably 10 wt.%. In this invention, the preparation method of the carbon / ceramic friction disk preferably includes chemical vapor deposition (CVI) + fused silica infiltration (RMI).
[0033] In this invention, the desiliconization pretreatment is preferably performed by acid etching or heat treatment. In this invention, the heat treatment temperature is preferably 1600~1800℃, more preferably 1700℃; the vacuum degree is preferably <100Pa, more preferably 10~90Pa, specifically preferably 10Pa, 20Pa, 30Pa, 40Pa, 50Pa, 60Pa, 70Pa, 80Pa, or 90Pa; the time is preferably 50~70min, more preferably 60min. In this invention, the reagent used for acid etching is preferably a mixed acid, which preferably includes hydrofluoric acid and nitric acid. The volume ratio of hydrofluoric acid to nitric acid in the mixed acid is preferably 1:2~4, more preferably 1:3; the mass concentration of hydrofluoric acid is preferably greater than or equal to 40%, and the mass concentration of nitric acid is preferably 65~68%. In this invention, the acid etching temperature is preferably room temperature, i.e., no additional heating or cooling is required; the time is preferably 90~150min, more preferably 120min.
[0034] In this invention, the desiliconization pretreatment removes free silicon from the micropores in the surface layer of the carbon / ceramic friction disc within 1-2 mm of the disc body surface. In this invention, the residual silicon content on the friction surface of the pretreated carbon / ceramic friction disc is ≤1.0%, specifically preferably 0.5%, 0.8%, or 1.0%.
[0035] After obtaining the pretreated carbon / ceramic friction disk, the present invention impregnates and seals the pretreated carbon / ceramic friction disk in a composite impregnation solution to obtain an impregnated carbon / ceramic friction disk. In the present invention, the composite impregnation solution is the impregnation and sealing solution for carbon / ceramic friction disks described in the above-described technical solution or the impregnation and sealing solution for carbon / ceramic friction disks prepared by the preparation method described in the above-described technical solution. In the present invention, the impregnation and sealing pressure is preferably 1.2~2.0 MPa, specifically preferably 1.2 MPa, 1.3 MPa, 1.4 MPa, 1.5 MPa, 1.6 MPa, 1.7 MPa, 1.8 MPa, 1.9 MPa, or 2.0 MPa; the time is preferably 60~120 min, specifically preferably 90 min. In the present invention, the impregnation and sealing is preferably performed in an impregnation device. In this invention, the specific process of impregnation and sealing is as follows: the pretreated carbon / ceramic friction disc is placed in an impregnation device and vacuumed; after vacuuming, a composite impregnation liquid is added, and nitrogen gas is introduced until the impregnation and sealing pressure is reached. In this invention, the vacuuming time is preferably 30-60 minutes, more preferably 45 minutes; the vacuum degree of the impregnation device after vacuuming is preferably ≤500 Pa, more preferably 100-500 Pa, and specifically preferably 100 Pa, 200 Pa, 300 Pa, 400 Pa, or 500 Pa. In this invention, the pressure and time settings for impregnation and sealing allow the composite impregnation liquid to fully penetrate the micropores and gaps on the surface of the pretreated carbon / ceramic friction disc, thereby achieving deep penetration of the composite impregnation liquid into the micropores of the friction surface and improving the densification effect.
[0036] After obtaining the impregnated carbon / ceramic friction disk, the present invention performs pyrolysis and curing on the impregnated carbon / ceramic friction disk to obtain a densified carbon / ceramic friction disk. In the present invention, the pyrolysis and curing temperature is preferably 1250~1450℃, specifically 1250℃, 1300℃, 1350℃, 1400℃, or 1450℃; the heating rate to the pyrolysis and curing temperature is preferably 5~10℃ / min, specifically 5℃ / min, 6℃ / min, 7℃ / min, 8℃ / min, 9℃ / min, or 10℃ / min; and the holding time is preferably 2~4 hours, specifically 3 hours. In the present invention, the pyrolysis and curing is preferably carried out under a protective atmosphere, which preferably includes nitrogen and / or argon. In this invention, the pyrolysis curing ensures that the polymer in the composite impregnation solution is fully pyrolyzed and cured to form a continuous ceramic phase, while avoiding microcracks in the sealing layer caused by excessively rapid heating. During the pyrolysis curing process, the polymer in the composite impregnation solution pyrolyzes and cures to form a SiC-Si3N4 multi-element ceramic phase, while the interface-reinforcing metal component reacts in situ with the carbon / ceramic friction disk matrix and SiC. The friction and wear-resistant ceramic component, the metal oxide modified component, and the SiC-Si3N4 multi-element ceramic phase interweave to form a dense composite sealing layer. After the pyrolysis curing is completed, the furnace is cooled to room temperature to obtain a dense carbon / ceramic friction disk.
[0037] After the pyrolysis and solidification, the present invention preferably further includes: after cooling to room temperature in the furnace, fine machining is performed. The fine machining preferably includes: grinding the friction surface and mounting reference surface of the pyrolysis and solidified carbon / ceramic friction disk, milling the mounting holes and positioning grooves, and chamfering to ensure the dimensional accuracy, form and position tolerances and surface quality of the carbon / ceramic friction disk, and to meet the assembly and performance requirements.
[0038] Figure 1 A flowchart of the impregnation and sealing method for the carbon / ceramic friction disc provided by the present invention.
[0039] The present invention also provides a densified carbon / ceramic friction disc obtained by the impregnation and sealing method described in the above technical solution.
[0040] The present invention also provides the application of the densified carbon / ceramic friction disc described in the above technical solution in high-speed braking or clutch transmission components.
[0041] In this invention, the densified carbon / ceramic friction disc is preferably used as a friction disc when applied to high-speed braking or clutch transmission components. In this invention, the high-speed braking preferably includes an aircraft brake disc, and the clutch transmission component preferably includes an aircraft engine clutch disc or an automotive high-speed clutch disc.
[0042] The following detailed description, in conjunction with embodiments, of the impregnation and sealing liquid and impregnation and sealing method of the carbon / ceramic friction disc provided by the present invention, as well as the densified carbon / ceramic friction disc and its application, should not be construed as limiting the scope of protection of the present invention.
[0043] Example 1 An impregnation and sealing process for the friction surface of a carbon / ceramic friction disc includes the following steps: 1. Silicon removal pretreatment: The carbon-ceramic friction disk is prepared using the industry-standard chemical vapor deposition (CVI) + fused silica infiltration (RMI) process. First, a carbon fiber preform is used as the skeleton. CVI deposition and pyrolysis of carbon are used for densification, followed by graphitization heat treatment to obtain a porous carbon / carbon blank. Finally, molten silica is infiltrated through RMI, where silicon reacts in situ with carbon to form silicon carbide, resulting in a carbon / ceramic friction disk with a residual silicon content of 10 wt.%. The carbon / ceramic friction disk is then subjected to vacuum heat treatment to remove silicon at 1700℃, a vacuum degree of 80 Pa, and a time of 60 min, yielding a pretreated carbon / ceramic friction disk with a residual silicon content of 0.8% on the friction surface.
[0044] 2. Preparation of the composite impregnation solution: Liquid polycarbosilane (number average molecular weight of 1000 g / mol) and liquid polyborosilicate (number average molecular weight of 1300 g / mol) were compounded at a mass ratio of 8:2 to form a polymer. Then, 3% by mass of an interface-reinforcing metal component (nano-Ti, Cr, and Ni powders compounded at a mass ratio of 4:4:2, particle size 50-200 nm), 4% by mass of a friction-resistant ceramic component (nano-SiC, ZrB2, and ZrC powders compounded at a mass ratio of 5:3:2, particle size 100-500 nm), and 3% by mass of a nano-scale metal oxide component (nano-CeO2 and Y2O3 powders compounded at a mass ratio of 3:2, particle size 50-100 nm) were added to the polymer and dispersed under ultrasonic power of 400 W and stirring speed of 1000 r / min for 60 min to obtain a uniform composite impregnation solution. The total mass percentage of the three functional components was 10%, not exceeding 15%.
[0045] 3. Impregnation and sealing: Place the pretreated carbon / ceramic friction disc and composite impregnation liquid into the impregnation equipment and perform vacuum evacuation for 45 minutes to achieve a vacuum degree of 300 Pa. After vacuum evacuation, use the composite impregnation liquid to impregnate and seal the friction surface, and introduce nitrogen gas to achieve a pressure of 1.6 MPa for 90 minutes.
[0046] 4. Pyrolysis and curing: The impregnated carbon / ceramic friction disk is transferred to a pyrolysis furnace and pyrolyzed and cured under an argon atmosphere with a gradient heating rate of 8℃ / min. The final pyrolysis and curing temperature is 1300℃, and the holding time is 3h. After the pyrolysis and curing is completed, the disk is cooled to room temperature with the furnace to obtain the impregnated and sealed carbon / ceramic friction disk, i.e., the densified carbon / ceramic friction disk.
[0047] The performance of the densified carbon / ceramic friction disc prepared in this embodiment was tested. The results were as follows: the interlaminar shear strength at room temperature was 42 MPa, as tested according to GB / T1448-2005; and the mass loss rate after high-temperature oxidation at 1300℃ for 10 hours was 1.9%, as tested according to GB / T13303-1991.
[0048] Example 2 An impregnation and sealing process for the friction surface of a carbon / ceramic friction disc includes the following steps: 1. Silicon removal pretreatment: The silicon-infiltrated carbon / ceramic friction disk is desiliconized by acid etching. The acid etching reagent is a mixed acid with a volume ratio of hydrofluoric acid to nitric acid of 1:3. The mass concentration of hydrofluoric acid is 40% and the mass concentration of nitric acid is 65~68%. The acid etching time is 120 min at room temperature to obtain a pretreated carbon / ceramic friction disk with a residual silicon content of 1.0% on the friction surface.
[0049] 2. Preparation of the composite impregnation solution: Liquid polycarbosilane (number average molecular weight of 900 g / mol) and liquid polyborosilicate (number average molecular weight of 1100 g / mol) were compounded at a mass ratio of 7:3 to form a polymer. 2% by mass of an interface-reinforcing metal component (nano-Ti, Cr, and Ni powders compounded at a mass ratio of 4:4:2, particle size 50-200 nm), 3% by mass of a friction-resistant ceramic component (nano-SiC, ZrB2, and ZrC powders compounded at a mass ratio of 5:3:2, particle size 100-500 nm), and 2% by mass of a nano-scale metal oxide modifying component (nano-CeO2 and Y2O3 powders compounded at a mass ratio of 3:2, particle size 50-100 nm) were added to the polymer and dispersed under ultrasonic power of 300 W and stirring speed of 800 r / min for 80 min to obtain a uniform composite impregnation solution. The total mass percentage of the three functional components was 7%.
[0050] 3. Impregnation and sealing: Place the pretreated carbon / ceramic friction disc into the impregnation equipment and vacuum-evacuate only the friction surface of the pretreated carbon / ceramic friction disc for 60 minutes to achieve a vacuum degree of 300 Pa. After vacuum evacuation, use a composite impregnation liquid to impregnate and seal the friction surface, and perform anti-impregnation treatment on the non-friction surface. Introduce nitrogen gas to achieve a pressure of 1.2 MPa for 120 minutes.
[0051] 4. Pyrolysis and curing: The impregnated carbon / ceramic friction disk is transferred to a pyrolysis furnace and pyrolyzed and cured under a nitrogen atmosphere with a gradient heating rate of 5℃ / min. The final pyrolysis and curing temperature is 1450℃, and the holding time is 4h. After the pyrolysis and curing is completed, the disk is cooled to room temperature with the furnace to obtain the impregnated and sealed carbon / ceramic friction disk, i.e., the densified carbon / ceramic friction disk.
[0052] The performance of the densified carbon / ceramic friction disc prepared in this embodiment was tested, and the results were as follows: interlaminar shear strength at room temperature was 36 MPa; mass loss rate after high-temperature oxidation at 1300℃ for 10 h was 2.1%.
[0053] Example 3 An impregnation and sealing process for the friction surface of a carbon / ceramic friction disc includes the following steps: 1. Desiliconization pretreatment: The silicon-dipped carbon / ceramic friction disk is subjected to vacuum heat treatment (temperature 1700℃, vacuum degree 80Pa, time 60min) to remove silicon, and a pretreated carbon / ceramic friction disk is obtained with a residual silicon content of 0.5% on the friction surface.
[0054] 2. Preparation of the composite impregnation solution: Liquid polycarbosilane (number average molecular weight of 1100 g / mol) and liquid polyborosilicate (number average molecular weight of 1400 g / mol) were compounded at a mass ratio of 9:1 to form a polymer. 5% by mass of an interface-reinforcing metal component (nano-Ti, Cr, and Ni powders compounded at a mass ratio of 4:4:2, particle size 50-200 nm), 6% by mass of a friction-resistant ceramic component (nano-SiC, ZrB2, and ZrC powders compounded at a mass ratio of 5:3:2, particle size 100-500 nm), and 4% by mass of a nano-scale metal oxide component (nano-CeO2 and Y2O3 powders compounded at a mass ratio of 3:2, particle size 50-100 nm) were added to the polymer and dispersed under ultrasonic power of 500 W and stirring speed of 1200 r / min for 40 min to obtain a uniform composite impregnation solution. The total mass percentage of the three functional components was 15%, which was the maximum allowed value.
[0055] 3. Directional impregnation and sealing of friction surfaces: Place the pretreated carbon / ceramic friction disc into the impregnation equipment and vacuum the friction surfaces for 30 minutes until the vacuum degree is 300 Pa. After vacuuming, use a composite impregnation liquid to impregnate and seal the friction surfaces, and perform anti-impregnation treatment on the non-friction surfaces. Introduce nitrogen gas to make the pressure 2.0 MPa for 60 minutes.
[0056] 4. Pyrolysis and curing: The impregnated carbon / ceramic friction disk is transferred to a pyrolysis furnace and pyrolyzed and cured under an argon atmosphere with a gradient heating rate of 10℃ / min. The final pyrolysis and curing temperature is 1450℃, and the holding time is 2h. After the pyrolysis and curing is completed, the disk is cooled to room temperature with the furnace to obtain the impregnated and sealed carbon / ceramic friction disk, i.e., the densified carbon / ceramic friction disk.
[0057] The performance of the densified carbon / ceramic friction disc prepared in this embodiment was tested, and the results were as follows: interlaminar shear strength at room temperature was 45 MPa; and the mass loss rate after high-temperature oxidation at 1300℃ for 10 h was 1.8%.
[0058] Comparative Example 1 An impregnation and sealing process for the friction surface of a carbon / ceramic friction disc includes the following steps: 1. Desiliconization pretreatment: The siliconized carbon / ceramic friction disk is subjected to vacuum heat treatment at a temperature of 1700℃, a vacuum degree of 80Pa, and a time of 60min to obtain a pretreated carbon / ceramic friction disk with a residual silicon content of 0.8% on the friction surface.
[0059] 2. Preparation of the composite impregnation solution: Liquid polycarbosilane (number average molecular weight of 1000 g / mol) was used as the polymer. 3% by mass of an interface-reinforcing metal component (nano-Ti, Cr, and Ni powders in a mass ratio of 4:4:2, particle size 50-200 nm), 4% by mass of a friction-resistant ceramic component (nano-SiC, ZrB2, and ZrC powders in a mass ratio of 5:3:2, particle size 100-500 nm), and 3% by mass of a nano-scale metal oxide component (nano-CeO2 and Y2O3 powders in a mass ratio of 3:2, particle size 50-100 nm) were added to the polymer and dispersed under ultrasonic power of 400 W and stirring speed of 1000 r / min for 60 min to obtain a uniform composite impregnation solution. The total mass percentage of the three functional components was 10%, not exceeding 15%.
[0060] 3. Impregnation and sealing: Place the pretreated carbon / ceramic friction disc into the impregnation equipment and perform vacuum evacuation for 45 minutes to a vacuum degree of 300 MPa. After vacuum evacuation, use a composite impregnation liquid to impregnate and seal the friction surface, and introduce nitrogen gas to make the pressure 1.6 MPa for 90 minutes.
[0061] 4. Pyrolysis and curing: The impregnated carbon / ceramic friction disk is transferred to a pyrolysis furnace and pyrolyzed and cured under an argon atmosphere with a gradient heating rate of 8℃ / min. The final pyrolysis and curing temperature is 1300℃, and the holding time is 3h. After the pyrolysis and curing is completed, the disk is cooled to room temperature with the furnace to obtain the impregnated and sealed carbon / ceramic friction disk, i.e., the densified carbon / ceramic friction disk.
[0062] The performance of the densified carbon / ceramic friction disc prepared in this embodiment was tested, and the results were as follows: the interlaminar shear strength at room temperature was 21 MPa; the mass loss rate after high-temperature oxidation at 1300℃ for 10 h was 4.8%.
[0063] Comparative Example 2 The difference from Example 1 is that the interface-enhancing metal component in the composite impregnation solution is omitted, while the rest is the same as in Example 1.
[0064] The performance of the densified carbon / ceramic friction disc prepared in this comparative example was tested. The results showed that the interlaminar shear strength at room temperature was 18 MPa, and the mass loss rate after high-temperature oxidation at 1300℃ for 10 h was 4.2%.
[0065] Comparative Example 3 The difference from Example 1 is that the friction-resistant ceramic component in the composite impregnation solution is omitted, while the rest is the same as in Example 1.
[0066] The performance of the densified carbon / ceramic friction disc prepared in this comparative example was tested. The results showed that the interlaminar shear strength at room temperature was 26 MPa, and the mass loss rate after high-temperature oxidation at 1300℃ for 10 h was 3.0%.
[0067] Comparative Example 4 The difference from Example 1 is that the nanoscale metal oxides in the composite impregnation solution are omitted, while the rest is the same as in Example 1.
[0068] The performance of the densified carbon / ceramic friction disc prepared in this comparative example was tested. The results showed that the interlaminar shear strength at room temperature was 29 MPa, and the mass loss rate after high-temperature oxidation at 1300℃ for 10 h was 2.5%.
[0069] As can be seen from the performance of the above embodiments and comparative examples, the present invention, through the polycarbosilane-polyborosilicate composite impregnation system, combined with the synergistic effect of interface-enhancing metal components, wear-resistant ceramic components and metal oxide components, significantly improves the interlaminar shear strength and oxidation resistance of the carbon / ceramic friction disc, resulting in better frictional stability.
[0070] The friction performance of the densified carbon / ceramic friction discs of Example 1 and Comparative Example 1 was tested according to GB / T40398.1-2021. The friction test conditions were: specific pressure 0.95 MPa, rotational speed 9000 r / min, and moment of inertia 0.2 kg·m. 2 The result is as follows Figures 2-4 As shown.
[0071] Comparative Example 1, lacking the addition of polyborosilazane, exhibited a single type of ceramic pyrolysis products, low matrix density, and numerous porosity defects. Consequently, it showed decreased strength, increased high-temperature oxidation channels, and significantly elevated oxidation weight loss. After multiple high-speed, heavy-load friction tests, severe oxidation occurred at both the inner and outer edges (e.g., ...). Figure 4 This is mainly due to the short bonding time, rapid temperature rise, and high oxygen concentration at the inner and outer edges under high-speed, heavy-load friction conditions. However, in Example 1, after an improved sealing process, no obvious oxidation signs were observed at the inner and outer edges after multiple high-speed, heavy-load friction tests, and a continuous friction film (such as...) formed on the entire friction surface. Figure 2 The coefficient of friction is stable with small fluctuations, exhibiting good frictional stability (e.g., Figure 3 ), further improving the operating temperature; among which Figure 3 The temperature tested was the temperature at the center of the stationary ring thickness, not the instantaneous local temperature of the friction surface. Infrared monitoring showed that the friction surface temperature could reach 750℃.
[0072] Comparative Example 2, lacking the addition of interface-reinforcing metal components, exhibits insufficient interfacial bonding between the carbon fiber and the ceramic matrix, leading to easy interface debonding and low interlaminar shear strength. Furthermore, the interface defects provide pathways for oxygen diffusion, significantly degrading its oxidation resistance. Comparative Example 3, without the addition of wear-resistant ceramic components, lacks a continuous wear-resistant and oxidation-resistant framework on its surface, resulting in decreased high-temperature wear and oxidation resistance, and also impacting its mechanical properties. Comparative Example 4, without the use of metal oxides, generally has larger grain sizes and more grain boundary defects, resulting in slightly lower overall performance than the examples, but superior to the other comparative examples.
[0073] In summary, all components and precursor systems of this invention are indispensable. Through synergistic effects, they achieve a unified approach to densification and pore sealing, interface strengthening, oxidation resistance, and frictional stability. The overall technical effect is significantly better than existing single-system solutions.
[0074] The above description is only a preferred embodiment of the present invention. It should be noted that for those skilled in the art, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.
Claims
1. An impregnation and sealing solution for a carbon / ceramic friction disc, characterized in that, The components include the following components by mass percentage: Interface-reinforcing metal component 2-5%, friction-resistant ceramic component 3-6%, metal oxide component 2-5%, balance polymer; The polymer comprises liquid polycarbosilane and liquid polyborosilicate, wherein the mass ratio of liquid polycarbosilane to liquid polyborosilicate is 7~9:1~3; The interface-enhancing metal component includes one or more of titanium powder, chromium powder, nickel powder, cobalt powder, and molybdenum powder; The friction-resistant ceramic component includes one or more of silicon carbide, zirconium boride, boron carbide, and zirconium carbide; The metal oxide component includes one or more of cerium oxide, yttrium oxide, and lanthanum oxide.
2. The impregnation and sealing solution for the carbon / ceramic friction disc according to claim 1, characterized in that, The total mass percentage of the interface-enhancing metal component, the tribologically resistant ceramic component, and the metal oxide component does not exceed 15%.
3. The method for preparing the impregnation and sealing liquid for the carbon / ceramic friction disk according to claim 1 or 2, characterized in that, Includes the following steps: The polymer, interface-reinforcing metal component, friction-resistant ceramic component, and metal oxide component are mixed and dispersed to obtain the impregnation and sealing liquid for the carbon / ceramic friction disk.
4. The preparation method according to claim 3, characterized in that, The composite dispersion is carried out under ultrasonic and stirring conditions, wherein the ultrasonic power is 300~500W, the stirring speed is 800~1200r / min, and the composite dispersion time is 40~80min.
5. A method for impregnating and sealing pores in a carbon / ceramic friction disc, characterized in that, Includes the following steps: The carbon / ceramic friction disk is pretreated with desiliconization to obtain a pretreated carbon / ceramic friction disk; The pretreated carbon / ceramic friction disk is impregnated and sealed in a composite impregnation solution to obtain an impregnated carbon / ceramic friction disk. The impregnated carbon / ceramic friction disk is pyrolyzed and solidified to obtain a densified carbon / ceramic friction disk. The composite impregnation liquid is the impregnation and sealing liquid for the carbon / ceramic friction disk as described in claim 1 or 2, or the impregnation and sealing liquid for the carbon / ceramic friction disk prepared by the preparation method described in claim 3 or 4.
6. The impregnation sealing method according to claim 5, characterized in that, The residual silicon content of the carbon / ceramic friction disc is 8~15 wt.%; The desiliconization pretreatment method is acid etching or heat treatment; The heat treatment temperature is 1600~1800℃, the vacuum degree is <100Pa, and the time is 50~70min; The reagent used for acid etching is a mixed acid, which includes hydrofluoric acid and nitric acid. The volume ratio of hydrofluoric acid to nitric acid in the mixed acid is 1:2~4. The mass concentration of hydrofluoric acid is greater than or equal to 40%, and the mass concentration of nitric acid is 65~68%. The acid etching time is 90~150 min.
7. The impregnation sealing method according to claim 5, characterized in that, The impregnation and sealing pressure is 1.2~2.0MPa, and the time is 60~120min.
8. The impregnation sealing method according to claim 5, characterized in that, The pyrolysis curing temperature is 1250~1450℃, the rate of heating to the pyrolysis curing temperature is 5~10℃ / min, and the holding time is 2~4h.
9. The densified carbon / ceramic friction disc obtained by the impregnation and sealing method according to any one of claims 5 to 8.
10. The application of the densified carbon / ceramic friction disc of claim 10 in a high-speed braking or clutch transmission assembly.